2019
DOI: 10.1242/dev.174508
|View full text |Cite
|
Sign up to set email alerts
|

A V0-ATPase-dependent apical trafficking pathway maintains the polarity of the intestinal absorptive membrane

Abstract: Intestine function relies on the strong polarity of intestinal epithelial cells and the array of microvilli forming a brush border at their luminal pole. Combining a genetic RNA interference (RNAi) screen with in vivo super-resolution imaging in the Caenorhabditis elegans intestine, we found that the V0 sector of the vacuolar ATPase (V0-ATPase) controls a late apical trafficking step, involving Ras-related protein 11 (RAB-11) + endosomes and the N-ethylmaleimide-sensitive factor-attachment protein receptor (SN… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 76 publications
4
35
0
Order By: Relevance
“…10 We therefore generated an endogenous IFB-2::mCherry fusion and analyzed the localization of BBLN-1 relative to IFB-2 and ERM-1, which localizes to microvilli. 29,30 Consistent with localization to the endotube, we found that BBLN-1 co-localized with IFB-2, basal to ERM-1 (Figures 2C and 2D). To determine whether BBLN-1 stably associates with the IF network, we performed fluorescence recovery after photobleaching (FRAP) experiments.…”
Section: Loss Of Bbln-1 Causes Cytoplasmic Invaginations Of the Intestinal Apical Membranesupporting
confidence: 78%
“…10 We therefore generated an endogenous IFB-2::mCherry fusion and analyzed the localization of BBLN-1 relative to IFB-2 and ERM-1, which localizes to microvilli. 29,30 Consistent with localization to the endotube, we found that BBLN-1 co-localized with IFB-2, basal to ERM-1 (Figures 2C and 2D). To determine whether BBLN-1 stably associates with the IF network, we performed fluorescence recovery after photobleaching (FRAP) experiments.…”
Section: Loss Of Bbln-1 Causes Cytoplasmic Invaginations Of the Intestinal Apical Membranesupporting
confidence: 78%
“…To confirm that BBLN-1 resides at the endotube, we generated an endogenous mCherry fusion of the intestinal intermediate filament protein IFB-2. We then analyzed the localization of BBLN-1 relative to IFB-2 and to ERM-1, which localizes apically at microvilli (Bidaud-Meynard et al, 2019; Ramalho et al, 2020). Consistent with localization to the endotube, we found that BBLN-1 colocalizes with IFB-2, basal to ERM-1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Loss of function mutations in syntaxin binding protein 2 result in familial hemophagocytic lymphohistiocytosis type 5, a disease that manifests gastrointestinal symptoms similar to MVID (Davidson et al, 1978;Côte et al, 2009;Pagel et al, 2012;Stepensky et al, 2013;Vogel et al, 2017;Mosa et al, 2018). Silencing of the V0-ATPase in Caenorhabditis elegans also revealed microvillus inclusion formation de novo in the cytoplasm or from internalization of large structures from the apical or basolateral plasma membrane (Bidaud-Meynard et al, 2019). The formation of microvillus-lined inclusions, best characterized in MVID, has been postulated to arise from nucleation in the cytoplasm or from internalization of the plasma membrane (Davidson et al, 1978;Cutz et al, 1989;Mosa et al, 2018;Bidaud-Meynard et al, 2019).…”
Section: Introductionmentioning
confidence: 99%